2021
DOI: 10.1002/brb3.2299
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala subnuclei development in adolescents with autism spectrum disorder: Association with social communication and repetitive behaviors

Abstract: Introduction:The amygdala subnuclei regulate emotional processing and are widely implicated in social cognitive impairments often seen in children with autism spectrum disorder (ASD). Dysregulated amygdala development has been reported in young children with ASD; less is known about amygdala maturation in later adolescence, a sensitive window for social skill development. Methods: The macrostructural development of the amygdala subnuclei was assessed at two time points in a longitudinal magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…From Golgi–Kopsch‐impregnated principal neurons data from the lateral amygdaloid nucleus, young autism spectrum disorder cases have a greater number of spines that tend to be more immature than in typically developing peers (Weir et al., 2017). The CoA is a candidate to be further studied in these cases because the increased growth of the right CoA volume positively predicted the impairment of social domain scores of children and adolescents on the Autism Diagnostic Observation Schedule‐G diagnostic test (Seguin et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…From Golgi–Kopsch‐impregnated principal neurons data from the lateral amygdaloid nucleus, young autism spectrum disorder cases have a greater number of spines that tend to be more immature than in typically developing peers (Weir et al., 2017). The CoA is a candidate to be further studied in these cases because the increased growth of the right CoA volume positively predicted the impairment of social domain scores of children and adolescents on the Autism Diagnostic Observation Schedule‐G diagnostic test (Seguin et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a hub in the "social brain, " the amygdala, which was located within the anterior medial portion of the brain's temporal lobe, maintains diverse connections with the neocortex, basal ganglia, hippocampus, thalamus, and other brain cortical areas via a network of white matter tracts, responsible for information processing that subserve emotional learning, social cognition, and social interaction (Baron-Cohen et al, 2000;Zalla and Sperduti, 2013;Ferrara et al, 2021;Raam and Hong, 2021;Xu et al, 2021). A large number of studies have demonstrated that amygdala structural and/or functional abnormalities are associated with social malfunctioning in ASD (Shen et al, 2016;Avino et al, 2018;Herrero et al, 2020;Xu et al, 2020;Seguin et al, 2021;Vitor-Vieira et al, 2021). So, we speculated that the prosocial behavior of AVP may be related to the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…17 An interesting experiment in animals' models documented that BLA is selectively affected by chronic stress and present microstructural alterations including dendritic hypertrophy and spine enlargement; these changes in turn correlated to the anxiety-like behaviours of the animals. 83 Recently, an enlargement of the BLA was positively correlated with social and communication impairments in adolescents with autism 84 and the deep brain stimulation of the BLA has been proposed as a possible treatment for social anxiety. 80…”
Section: Relationship Between Amygdala Subnuclear Volumes and Clinica...mentioning
confidence: 99%